Chemical bonding, thermodynamic stability and mechanical strength of Ni3Ti/α-Al2O3 interfaces by first-principles study. (1st January 2021) - Chen, Lu; Li, Yefei; Xiao, Bing; Gao, Yimin; Wang, Juan; Yi, Dawei; Wang, Zhicheng; Zhao, Siyong
Abstract: We performed a first-principles calculation to investigate the 85 different Ni3 Ti/Al2 O3 interfaces. The study shows that the formation of metal-oxygen interfaces and high symmetric interfacial stacking sequences is highly favored both by work of adhesion and interfacial energy. At high temperature and O-poor condition, the metal-metal interfaces show higher thermodynamic stability than metal-oxygen interfaces. The first principles tensile test predicts that the main cause of mechanical failure in Ni3 Ti/Al2 O3 interface is attributed to the breaking of the Ti-Ni bonds proximity to the interface in the bulk Ni3 Ti phase. Graphical abstract: The interfacial energies of the Ni&Ti-Al2 interfaces at 1000K are increased with the increasing of the partial pressure of oxygen, while for Ni&Ti-O interfaces which are decreasing. Image, graphical abstract